How to Operationalize IMF Engagement on Social Spending during and in the aftermath of the COVID-19 Crisis - Yackovlev, Irene; Liu, Fei.; Minasyan, Gohar; Murgasova, Zuzana (Washington, D.C. : International Monetary Fund, 2020)
How to Operationalize IMF Engagement on Social Spending during and in the aftermath of the COVID-19 Crisis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet